Formulasi Pendidikan Pesantren Dalam Uu Nomor 18 Tahun 2019 Tentang Pesantren (Tinjauan Kebijakan Pendidikan) - Idam Mustofa (Prodi Manajemen Pendidikan Islam STAI Darussalam, 2020)
The long journey of Islamic boarding schools in Indonesia has obtained regulations in the form of Law Number 18 of 2019 which binds the delivery of education as part of education policy. The formulation of the pesantren law has gone through a policy formulation process involving pesantren stakeholders and has received political support so that pesantren education policies can guarantee the sustainability of pesantren characteristics and traditions, such as the role of Majlis Masyayikh in guaranteeing the quality of education in the development of the pesantren curriculum. After the pesantren law was passed, there were several benefits in implementing the pesantren law, including: 1) state recognition of pesantren graduates; 2) guarantee the uniqueness of the pesantren in developing da'wah to spread Islamic teachings; and 3) opening up wide opportunities for pesantren for community empowerment.